Detecting Duplication in Students’ Research Data: A Method and Illustration - Allen, Peter; Lourenco, A.; Roberts, Lynne (Routledge, 2015)
Research integrity is core to the mission of higher education. In undergraduate student samples, self-reported rates of data fabrication have been troublingly high. Despite this, no research has investigated undergraduate data fabrication in a more systematic manner. We applied duplication screening techniques to 18 data sets submitted by psychology honors students for assessment. Although we did not identify any completely duplicated cases, there were numerous partial duplicates. Rather than indicating fabrication, however, these partial duplicates are likely a consequence of poor measure selection, insufficient data screening, and/or participant characteristics. Implications for the teaching and supervision of honors students are discussed.